Implementasi Corporate Social Responsibility-CSR PT X Dalam Meningkatkan Reputasi Perusahaan - Yunus Majd; Atma Purnama (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2023)
The CSR program is a business commitment to act ethically, legally, and contribute to improving the quality of life of the workforce as well as their families, local communities and the wider community. According to Marnelly (2012), the CSR concept involves responsible partnerships between government, companies and local communities that are active and dynamic. CSR is an action carried out by business actors or stakeholders through responsible behavior towards society. Business people focus their attention on 3 things, namely economic, social and environmental. This is focused as a mutually sustainable activity and improving reputation is one way to prevent crises (Sari, 2010)